A case of pelvic giant cell tumor of bone, complete remission with denosumab: long duration of response. Issue 5 (June 2020) - Bilgetekin, Irem; Mammadkhanli, Orkhan; Basal, Fatma Bugdayci; Kandemir, Olcay; Canbay, Suat; Oksuzoglu, Berna
Abstract : Although giant cell tumor of bone has been considered as a disease with benign course, it can lead to bone destruction and serious morbidity. A 19-year-old case was presented with hip pain. There was a recurrence after 9 months of curative surgical resection and zoledronic acid use, and as surgical morbidity would be high, antiosteoclastic receptor activator of nuclear factor kappa B ligand inhibitor denosumab treatment was administered. She had a complete remission after 18 months of denosumab treatment. The important point in the present case is that it has been followed up without recurrence after around 42 months of denosumab use and 11 months of follow-up after the cessation of drug. In recurrent cases in which nonmetastatic surgery is not suitable, the use of denosumab decreases tumor progression. The duration of use in unresectable and advanced cases still remains unclear.